2018
DOI: 10.7150/ijbs.25081
|View full text |Cite
|
Sign up to set email alerts
|

Construction of implantation failure related lncRNA-mRNA network and identification of lncRNA biomarkers for predicting endometrial receptivity

Abstract: Insufficient endometrial receptivity is a major factor leading to implantation failure (IF), and the traditional way of morphological observation of endometrium cannot determine the condition of receptivity sufficiently. Considering that long-noncoding RNAs (lncRNAs) regulate endometrial receptivity and competing endogenous RNA (ceRNA) mechanism works in plenty of biological processes, ceRNA is likely to function in the pathology of IF. In the present study, we aim to construct an implantation failure related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 69 publications
0
36
0
1
Order By: Relevance
“…In previous studies, many groups conducted bioinformatics analysis for lncRNAs using their co-expressing genes. For instance, Feng et al (2018) identified and predicted the functions of implantation failure related lncRNAs by constructing the lncRNA-mRNA co-expression network. In order to study the potential functions of atherosclerosis-related lncRNAs, we performed WGCNA analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, many groups conducted bioinformatics analysis for lncRNAs using their co-expressing genes. For instance, Feng et al (2018) identified and predicted the functions of implantation failure related lncRNAs by constructing the lncRNA-mRNA co-expression network. In order to study the potential functions of atherosclerosis-related lncRNAs, we performed WGCNA analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the specific functions of most lncRNAs are still unknown, recent studies have shown that lncRNAs play an important role in the development and progression of abortion . Feng et al clarified that many lncRNAs are abnormally expressed in patients with recurrent spontaneous abortion and that lncRNA can be used as a biomarker for predicting recurrent spontaneous abortion. A study by Zhang et al suggested that lncRNAs HOTAIR may be a potential therapeutic target for recurrent miscarriage.…”
Section: Discussionmentioning
confidence: 99%
“…,23 Feng et al24 clarified that many lncRNAs are abnormally expressed in patients with recurrent spontaneous abortion and that lncRNA can be used as a biomarker for predicting recurrent spontaneous abortion. A studyby Zhang et al 25 suggested that lncRNAs HOTAIR may be a potential therapeutic target for recurrent miscarriage.…”
mentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are more than 200 nucleotides in length and do not code for proteins (Ponting et al, 2009), and involved in the regulation of diverse biological processes including carcinogenesis, epigenetic regulation, and embryonic development (Wapinski and Chang, 2011;Batista and Chang, 2013). Using high-throughput sequencing analysis, recent studies have attempted to uncover key lncRNAs as biomarkers to predict endometrial receptivity (Koot et al, 2016;Fan et al, 2017;Sigurgeirsson et al, 2017;Chen et al, 2018Chen et al, , 2019Feng et al, 2018), while little is known about their biological function and significance in the human endometrium. The expression of H19 was down-regulated in the endometrium of RIF (Zeng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%